Decreasing Blood Pressure: One bite of chocolate at a time - Gillies, Chelsea; Konji, Sandra (Université d'Ottawa | University of Ottawa, 2015)
Context:  Dark chocolate consumption has been shown to have positive benefits on health. It has been hypothesised to decrease blood pressure, due to the high flavonoid content. The flavonoids in dark chocolate have been speculated to decrease platelet adhesion, and LDL levels, as well as enhance vasodilation. However, studies conducted have been inconclusive. Objective: To investigate the relationship between consumption of dark chocolate and blood pressure, among those with hypertension. Methods: A structured literature review, using the uOttawa library database, was conducted using studies published between 2005-2015. Articles written in English were analyzed. The keywords used were ‘dark chocolate’, ‘hypertension’, and ‘LDL’. Only peer reviewed papers, with experiments conducted on pre-hypertensive and hypertensive humans were considered. After applying this search parameters, 11 articles remained.. Results: Among consumers, most of the articles illustrated a positive correlation between dark chocolate consumption, lowered LDL levels, increased flow-mediated dilation and lowered blood pressure levels overall. However, most of these studies were conducted on small sample sizes, with a small amount of dark chocolate consumed. The aforementioned effects were only observed for a short period of time. Conclusion: Therefore, it can be concluded that short term dark chocolate consumption has been shown to decrease LDL levels, and induce vasodilation, thus lowering hypertension among the selected population.